Indirect commercialization of psychological research based on results of the DESMoPsI project - Kozłowska, Agata (Przegląd Psychologiczny, 2021)
Objective The paper focuses on the concept of commercialization and the specificity of commercialization processes in social sciences. In line with the Knowledge Triangle approach which underpins the majority of modern scientific policies, universities should integrate their activities in research, education and innovation. Commercialization of research is an example of such activity. Commercialization may proceed in a direct manner, when the university assumes control over the implementation process, either independently or through a special-purpose vehicle. Research results can also be commercialized indirectly by spin-off organizations that are established specifically for this purpose and operate on market principles. Theses 1) The results of research in social sciences are incorrectly perceived as having negligible potential for commercialization. 2) Researchers involved in indirect commercialization projects face numerous competence and organizational challenges. Conclusions An analysis of the research project conducted in 2015–2018 by the Faculty of Psychology of the SWPS University of Social Sciences and Humanities in Warsaw with the aim of developing a digital platform for designing, sharing and evaluating online psychological interventions (DESMoPsI, market label: Beviado) revealed the challenges that are faced by scientists who are involved in the indirect commercialization of research results. To guarantee the success of such projects, members of the academic community should be able to identify market requirements, develop market communication skills, and improve their knowledge of law and finance.